Doing Business in Nigeria 2010 - World Bank; International Finance Corporation (Washington, DC, 2013)
Doing Business in Nigeria 2010 is the second subnational report of the Doing Business series in Nigeria. In 2008, quantitative indicators on business regulations were created for 10 states and Abuja, FCT. This year, Doing Business in Nigeria 2010 expands the analysis to all 36 Nigerian states and Abuja, FCT, and documents progress in the 10 states and the capital previously measured. The states are compared against each other, and with 183 economies worldwide. Doing Business investigates the regulations that enhance business activity and those that constrain it. Regulations affecting 4 stages of the life of a business are measured at the subnational level in Nigeria: starting a business, dealing with construction permits, registering property, and enforcing contracts. These indicators have been selected because they cover areas of local jurisdiction or practice. The data in Doing Business in Nigeria 2010 are current as of January 2010.